Hubungan antara Kualitas Pelayanan Patient Relations Rumah Sakit Pondok Indah dengan Sikap Pasien terhadap Rumah Sakit - Khaliaphnie, Anisah; Setianti, Yanti; Agung Prastowo, FX.Ari (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
Communication between patients and doctors has become a problem in most cases. Communication between doctors and patients in Indonesia has not been a major concern. So far, communication competence tends to be neglected. Though communication between patient and doctor is an important factor in order to support patient recovery.This study aims to determine the relationship between reliability, responsiveness, assurance, empathy and physical proof of Patient Relations RS Pondok Indah with patient attitude toward the hospital. The theory used is the theory of social exchange proposed by Thibault and Kelley.From the results of research conducted by the author on the Quality of Service Patient Relations Hospital Pondok Indah with Patient Attitudes toward the Hospital, it is concluded that the reliability of Patient Relations Pondok Indah Hospital has a very strong relationship with the attitude (cognition, affection and konasi) patients. This means the reliability provided by Patient Relations Officer which is a sub variable of the quality of this service can give effect to the patient's final attitude toward the hospital.